Simulation of Ionizing/Displacement Synergistic Effects on NPN Bipolar Transistors Irradiated by Mixed Neutrons and Gamma Rays - Yuhao Shan; Yanfei Liu; Hao Zheng; Zheng Peng (Science and Technology of Nuclear Installations)
Transistors working in complex radiation environments such as space are simultaneously irradiated by neutrons and gamma rays. But the mechanism of the synergistic radiation effect between the two rays is still unclear. Based on TCAD, the synergistic radiation effects of ionizing/displacement damage caused by mixed neutrons and gamma rays are simulated. The results demonstrate that the synergistic effects are more serious than the simple sum of the two radiation effects due to their mutual enhancement. The change of the carrier recombination rate in the device at different positions shows that the displacement effects increase the peak value of surface recombination rate; meanwhile, the ionizing dose effects enhance the recombination process in bulk silicon. The mechanism of this phenomenon is that positive charges from the oxide layer and interface enhance the recombination of carriers in bulk, and the reduced carrier lifetime caused by defects from bulk makes carriers more likely to be trapped by the interface traps. In addition, the simulation result which shows the influence of temperature on the synergistic effects indicates that the synergistic effects are more sensitive to the lower temperature.